2018
DOI: 10.1097/md.0000000000011266
|View full text |Cite
|
Sign up to set email alerts
|

Effect of neuromuscular electrical stimulation for endometriosis-associated pain

Abstract: This retrospective study evaluated the effect of neuromuscular electrical stimulation (NMES) for the treatment of endometriosis-associated pain (EAP).A total of 154 patients with EAP were included and were divided into 2 groups in this retrospective study. Eighty-three patients were assigned a treatment group, and underwent NMES therapy, while 71 subjects in the control group were at waiting list. The primary outcome of pain was measured by the numerical rating scale (NRS) and the Endometriosis Symptom Severit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Women with DIE reported constipation, defecation pain, appetite disorders, longer evacuation time, and increased stool consistency without laxatives ( 21 ). Neuromuscular electro-stimulation was found to be an efficient method for alleviating endometriosis-related pain ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Women with DIE reported constipation, defecation pain, appetite disorders, longer evacuation time, and increased stool consistency without laxatives ( 21 ). Neuromuscular electro-stimulation was found to be an efficient method for alleviating endometriosis-related pain ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously believed that NMES can stimulate the shallow and deep pelvic oor muscles and nerves of the pelvic oor through lowfrequency pulses, promote the contraction of muscle groups, especially the contraction and muscle strength of the shallow and deep I and II muscle groups, which has a positive effect on postpartum urinary incontinence [31] [32]and after cervical cancer operation [33]. Besides, other studies believe that it plays a positive role in promoting the blood supply and lymphatic circulation of pelvic oor tissues and organs which can effectively reduce the pain caused by uterine contractions [10]. On the other hand, NMES can promote the smooth muscle relaxation of the uterine artery, reduce the resistance of uterine artery blood ow, accelerate the blood ow velocity, thus promoting the growth of endometrium or improving the local blood ow perfusion of the uterus, which is conducive to the repair of the endometrium.…”
Section: Discussionmentioning
confidence: 99%
“…Neuromuscular electrical stimulation(NMES), also known as biomimetic electrical stimulation, refers to the use of low-frequency pulse current to stimulate muscle or nerve, cause muscle contraction, increase blood circulation and nutrition supply, promote the recovery of nerve function, and then achieve the purpose of repair [6]. Previous researches have shown that neuromuscular electrical stimulation has positive effects on alleviating postpartum lumbar and back pain [7], the recovery of postpartum rectus muscle strength [8], and the improvement of endometrial thickness in pregnant patients [9],and reduce the pain of patients with endometriosis [10], etc. However, there are few studies on the prevention of complications after arti cial abortion.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies documented the effect of NMES in reducing pain in spinal cord injury [19,20], neck pain [21], patellofemoral pain [22], shoulder pain [23], and pain associated with endometriosis [24]. AVN is characterized by inflammatory changes and ischemia, which occur in the first stage and progresses to pain and edema.…”
Section: Discussionmentioning
confidence: 99%